THE EFFECT OF TASK-BASED LEARNING ON STUDENTS’ VOCABULARY SKILL AT MA DARUL ULUM PALANGKARAYA - Eri Nurianti; Abdul Syahid; Hesty Widiastuty (IKIP Siliwangi, 2022)
This research was motivated by the problems faced by some students in learning English. The problem that generally occurs was difficulty in English vocabulary. This objective in study was measured the effectiveness of Task-Based Learning on students’ vocabulary skill. on class XII students at MA Darul Ulum class 2020/2021 in Palangka Raya. This study used quantitative research methods with a quasi-experiment design. Researchers did the treatment and calculated the results of their pre-test and post-test scores. The researchers used two classes as samples where these two classes were from the control class and the experimental class which consisted of 56 people. the results of the analysis obtained a significance value of 0.02, it shows that the null hypothesis is rejected and the alternative hypothesis is accepted. In addition, the average value of the initial test of the experimental class was 49.92 and their scores increased on the post-test results to 72.92. Keywords: Task-Based Learning, Vocabulary Skill, Experiment Study